‘To what extent does Amazon.com, Inc success be accredited to its organizational culture and ND Jeff Bezos's leadership style? - SOLANKI, KALPANA (Archives of Business Research, 2019)
This research aims at finding the answer to the research ‘To what extent does Amazon.com, Inc's success be accredited to its's organizational culture and ND Jeff Bezos's leadership style? This research question is answered by using the concepts of Business management for identifying the organisational culture of Amazon and leadership style od Jeff Bezzo and later identify the role of the corporate culture and leadersip style in the success of Amazon. The secondary research shows that Amazon has an extremenly positive and welcoming organizational culture along with effective leadership style of Jeff bezzo which has led to the success of the company. Organisational culture motivate the human resources of the company to give their best efforts towards excellent customer services and customer satisfaction. The CEO jeff has inculcated a warn culture by injecting his values and used a mix of Authoratirian and democratic leadership style which has led to the success of the company. Human resources are the most important asset of every organisation and the positive organisational culture has contributed to the optimum utilization of the human resource capabilities in Amazon. The research essay end with the finding that the visonary leadership style of Jeff has inducted the long term values in the employees of Amazon. Amazon’s organisational culture can be depicted in the rituals, stories, behavior, communication, style, workplace practices, celebrations and dress code of the employees and management